ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI E-WOM DI RESTORAN DOMICILE KITCHEN AND LOUNGE SURABAYA - Ida Fitriani; Erna Andajani; Siti Rahayu (CALYPTRA, 2018)
Thepurposeofthis research is tounderstand and analyze the influence the factors that may influence tourist Elrctronic Word Of Mouth about restaurants Domicile Kitchen and Lounge Surabaya implying on the critical role of relationship quality. A structural equation modelling procedure is applied to this research. Data processing was conducted using SPSS 18 for Windows and Amos Graphic 20 for Windows. The sampling techniquethatused is convenience sampling type. 150respondents for restaurant Domicile Kitchen and Lounge. qualify the specifiedcharacteristicsof the population were the total ofsampleused in this research whichdistributed by offline quetionaire. The paper found that food quality, personal interaction quality, physical environment quality and perceived value influence e-WOM behavior of customer in an direct way through relationship quality.